Could ginger extract be a therapeutic drug for migraine? (Sciences of Phytochemistry, 2023)
Migraine is a common neurological disorder that may be accompanied by vascular disturbances, Migraine is one of the most causes of disability worldwide. Zingiber officinale is a medicinal herb that has an analgesic effect on many disorders such as headaches, migraine, muscle tension, stomach spasm, and dysmenorrhea. Also, ginger has many pharmacological actions used to treat and prevent various common symptoms and diseases. This review aims to evaluate the potential of ginger to treat or prevent migraine episodes. Especially nowadays, Patients prefer herbal and complementary medicine to avoid the hard side effects of chemical drugs. The author searched several databases including PubMed, Science Direct, Wiley Online, and Scopus through February 2023 for recent articles with good quality evaluating the potential of ginger to treat migraine patients. The author made investigations and Interpretations depending on the results of the authors' experiments in previous articles included in my review. It is suggested that the bioactive compounds in ginger have the potential to treat and prevent acute migraine episodes effectively and safely. The author recommends encouraging the manufacturing of different pharmaceutical dosage forms of ginger extract to be used worldwide in a safe way and to render a higher absorption rate, and pharmacological response.